STRATEGY OF EDUCATIONAL INSTITUTIONS IN CREATING RELIGIOUS CULTURE IN THE DISRUPTION ERA - Pramitha, Devi; Luthfita, Illa Zahroh (Proceeding of International Conference on Islamic Education (ICIED), 2022)
The existence of the era of disruption is certainly an opportunity as well as a challenge for Islamic Education institutions to optimize their resources, one of which is to make a strategic design to be ready to compete and survive in this era. The strategy of Islamic Education Institutions to create a religious culture becomes a reference for the formation of people with character, excellence and innovation. To be able to realize religious culture in Islamic educational institutions as the goal of education, namely by providing general knowledge accompanied by knowledge of religion (spiritual) so that it can overcome the moral crisis that hit this nation. School culture can be realized through the authority and responsibility of the principal as a leader, namely by compiling management from planning, implementation to evaluation. The method used in writing this article is a literature study or literature study. Literature study begins by collecting books and various national and international journal reports related to the problem to be solved, then compiled to draw conclusions. The compilation results from several journals and other supporting books are used to conclude information related to the process of principals in realizing a religious culture in schools. From this discussion it can be concluded the strategy that can be done by educational institutions in creating a religious culture is to develop efforts in 5 aspects, namely: (a) Religious practice (the ritualistic dimension ); (b) Religious belief (the ideological dimension ); (c) Religious knowledge (the intellectual dimension); (d) Religious feeling (the experiential dimension) ; and (e) Religious effect (the consequential dimension).